Recanalization of Chronic Occlusion of the Middle Cerebral Artery With Tissue Plasminogen Activator Treatment: A Case Report. Issue 4 (July 2018) - Lee, Seung Jae; Cheong, Jin Sung; Ryu, Han Uk; Kang, Hyun Goo
Abstract : Objectives: Patients with chronic proximal middle cerebral artery (MCA) occlusion do not present with severe symptoms, but early recanalization of acute occlusion is associated with high morbidity and mortality. Tissue plasminogen activator (tPA) is a recombinant thrombolytic agent approved for treating ischemic stroke, although only a few cases of tPA administration in chronic MCA occlusion have yielded positive results. Methods: A 71-year-old patient had a history of right MCA territorial infarction with the occlusion occurring 12 years ago (November 2005). Although the patient was treated with antiplatelet agents, MCA recanalization was not achieved. The patient was referred to our hospital again (January 2017) for newly discovered symptoms. We immediately administered tPA because the patient presented 2 hours after onset of symptoms. Results: Neurological symptoms resolved within 24 hours of treatment, and magnetic resonance angiography confirmed recanalization of the right MCA territorial lesion. No neurological abnormalities were observed during the 12-week follow-up. Conclusions: At present, tPA is the only approved treatment for acute ischemic stroke, although it presents a limited time frame to avoid severe medication-related adverse effects. Our report suggests nonatherosclerotic chronic MCA occlusion as an alternative application of tPA therapy.